The NK1 receptor antagonist aprepitant does not alter the pharmacokinetics of high-dose melphalan chemotherapy in patients with multiple myeloma - Egerer, Gerlinde; Eisenlohr, Kathrin; Gronkowski, Martina; Burhenne, Jürgen; Riedel, Klaus-Dieter; Mikus, Gerd (British journal of clinical pharmacology, 2010)
What is already known about this subject: Nausea and vomiting are the most distressing side-effects of a high dose melphalan regimen. Aprepitant in addition to an antiemetic standard regimen has been reported to improve significantly both acute and delayed chemotherapy-induced nausea and vomiting. - What this study adds: Anti-emetic regimens including aprepitant have no clinically relevant effect on the pharmacokinetics of the anticancer agent melphalan when administered 1 h before high dose melphalan infusion. - Aims: The objective of this investigation was to assess the effect of aprepitant on the pharmacokinetics of high-dose melphalan used as conditioning therapy before blood stem cell transplantation in multiple myeloma. - Methods: Aprepitant (125 mg) or placebo was administered 1 h before melphalan therapy (1 h infusion of 100 mg m−2). Eleven plasma samples were obtained over 8 h and melphalan was quantified using an LC/MS/MS method. Standard pharmacokinetic parameters were calculated and nonparametric testing was applied to assess the differences between aprepitant and placebo treatment. - Results: Twenty patients received placebo and 10 patients aprepitant treatment. There were no differences observed for Cmax at the end of melphalan infusion (placebo 3431 ± 608 ng ml−1vs. aprepitant 3269 ± 660 ng ml−1). In addition, AUC and terminal elimination half-life were not changed by aprepitant. Total clearance of melphalan was 304 ± 58 ml min−1 m−2 (placebo) which was not influenced by aprepitant (288 ± 78 ml min−1 m−2). - Conclusions: The administration of the NK1 receptor antagonist aprepitant 1 h before a high-dose chemotherapy does not influence the exposure and the elimination of melphalan. Therefore, oral administration of 125 mg aprepitant 1 h before melphalan infusion does not alter the disposition of intravenously administered melphalan.